Converge : the adaptive reuse of the Sunnyside galleries as a point of cultural convergence for the purpose of fostering social cohesion within interior spaces - Konigk, Raymund (University of Pretoria, 2015)
Dissertation (MInt(Prof))--University of Pretoria, 2014.